Partial differential equations : theory and completely solved problems - Hillen, Thomas, 1966-; Leonard, I. Ed., 1938-; Van Roessel, Henry, 1956- (Hoboken, N.J. : Wiley, 2012)
"Combining over 28 years of teaching experience, the authors present a PDE text that is accessible to all students--regardless of their background or mathematical sophistication. The book provides over 150 completely worked problems with solutions and commentaries for both linear partial differential equations and boundary value problems with applications in engineering and biology. Topics covered include a classification of PDEs, heat equation, wave equation, Laplace's equation, separation of variables, Fourier series, classical PDEs, Sturm-Liouville problems, special functions, transform methods, and the method of characteristics for first order PDEs"--
-- Table Of Contents: Preface Part I THEORY 1 Introduction 2 Fourier Series 3 Separation of Variables 4 Sturm-Liouville Theory 5 Heat, Wave, and Laplace Equations 6 Polar Coordinates 7 Spherical Coordinates 8 Fourier Transforms 9 Fourier Transform Methods in PDEs 10 Method of Characteristics Part II EXPLICITLY SOLVED PROBLEMS 11 Fourier Series Problems 12 Sturm-Liouville Problems 13 Heat Equation Problems 14 Wave Equation Problems 15 Laplace Equation Problems 16 Fourier Transform Problems 17 Method of Characteristics Problems 18 Four Sample Midterm Examinations 19 Four Sample Final Examinations Appendix A Gamma Function Bibliography Index
Includes bibliographical references and index.
Keywords: Differential equations, Partial